ADMINISTRATORS’ INSTRUCTIONAL LEADERSHIP AFFECTING INSTRUCTIONAL BEHAVIOR OF ENGLISH LANGUAGE TEACHER (THE FIRST AND SECOND LEVEL STUDENTS) IN BASIC EDUCATION SCHOOLS UNDER NAKHONSAWAN PRIMARY EDUCATIONAL SERVICE AREA OFFICE 2) - Pongpanukun, Kunlaya (Journal for Developing the Social and Community, 2020)
The objectives of this research were 1) to study administrators’ instructional leadership affecting Instructional and behavior of English language teacher (The First and Second level students) in basic education schools under Nakhonsawan Primary Education Service Area Office 2, 2) to study the relationship between Administrators’ instructional leadership affecting instructional behavior of English language teacher (The first and second level students) in basic education schools under Nakhosawan Primary Education Service Area Office 2 and 3) to create an equation to forecast administrators’ instructional leadership to behavior of English language teacher (The First and Second level students) in basic education schools under Nakhonsawan Primary Education Service Area Office 2. The results of the study were as follows: Administrators’ instructional leadership and instructional behavior of English language teacher (The first and second level students) were at a high level. The relationship of administrators’ instructional leadership and instructional behavior of English language teacher (The first and second level students) had a positive correlation and at the moderate level with a statistically significant at .01 level. The variables necessary for forecasting instructional behavior of English language teacher (The first and second level students) were consisted of considering paired aspects was planning to strengthen teachers to be professional, tendency of curriculum changing and teaching evaluation of teachers respectively. The value of Cronbach’s Alpha was 41.10 percent (Adjusted R square =.411) at the .05 level of significance. The equation of forecasting could be formed as follows: The forecasting equation by raw score: Y ̂= 1.103 + 0.282(X4) + 0.187(X1) + 0.158(X3) The forecasting equation by standard score: Z ̂ = 0.287(X4) + 0.186(X1) + 0.170 (X3)